VALIDATION AND APPLICATION OF RP-HPLC METHOD FOR QUANTIFICATION OF ENROFLOXACIN IN PURE AND VETERINARY DOSAGE FORMS - S. R., ASWATHY; C., MUHAS; SRUTHY S., ANJALI; P. V., DEVI SWAPNA; U., GOPINATH (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Objective: The main objective of this study is to develop and validate a simple, new, fast, sensitive, precise and accurate RP-HPLC analytical methods have been established for the estimation of enrofloxacin in bulk and pharmaceutical dosage forms. Methods: The present method was developed and validated on a Waters HPLC system using Phenomenex make Shimadzu C18 column (250 mm × 4.6 mm i.d., 5μm particle size) column was used for the separation. Best results were obtained with the mobile phase composition consisting of Acetonitrile-water (80:20, v/v). The system was regulated at 1.0 ml/min flow rate at 270 nm UV detection. Results: Enrofloxacin was eluted at 3.405 min retention time. The analytical parameters such as accuracy, precision, linearity, LOD, LOQ, ruggedness, and robustness were used for validating the developed method according to ICH guidelines. Linearity was exhibited over the concentration range of 0.1-0.6µg/ml and the Limit of Detection and Quantitation values for Enrofloxacin was 0.001µg/ml and 0.03µg/ml, respectively. The result of the analysis shows that the amount of drugs present in the formulation has a very good correlation with the label claim of the formulation and %RSD will be less than 2 for all the validation parameters. Recoveries studies revealed that results within the specified limits. Conclusion: The developed methods were validated for various parameters as per ICH guidelines. Hence the proposed method was found to be satisfactory and could be used for the routine analysis of enrofloxacin in their marketed formulation.